Low prevalence of archived integrase strand transfer inhibitors resistance associated mutations in Botswana before the roll out of dolutegravir based first line antiretroviral therapy - Maruapula, Dorcas; Ditshwanelo, Doreen; Pema, Marea N.; Bareng, Ontlametse T.; Choga, Wonderful T.; Moraka, Natasha O.; Mokgethi, Patrick T.; Seatla, Kaelo K.; Koofhethile, Catherine K.; Zuze, Boitumelo J.; Gaolathe, Tendani; Pretorius-Holme, Molly; et al. (Frontiers in Microbiology, 2024)
Background We evaluated the prevalence of archived proviral drug resistance mutations (DRMs) associated with resistance to integrase strand transfer inhibitors (INSTIs) shortly before Botswana transitioned in 2016 to using dolutegravir (DTG)-based antiretroviral treatment in first-line regimens. Methods We used the Stanford University HIV drug resistance database to analyze INSTI-resistance associated mutations (RAMs) in a large representative population-based cohort of adults recruited in 30 geographically dispersed communities as part of the Botswana Combination Prevention Project (BCPP) cohort from 2013 to 2018. A total of 5,144 HIV-1 proviral DNA sequences were included in our analysis; 1,281 sequences were from antiretroviral therapy (ART)-naïve individuals and 3,863 sequences were from non-nucleoside reverse transcriptase inhibitor (NNRTI) ART-experienced individuals. None of the sequences were from DTG-ART experienced participants. Results The overall prevalence of major INSTIs DRMs was 1.11% (95% CI 0.82–1.39%). The prevalence of INSTI DRMs in ART-naïve individuals was 1.64% (21/1,281) and 0.93% (36/3,863) in ART-experienced individuals. Major INSTI-RAMs detected in ART-naïve individuals were E138K (2/1,281; 0.16%), G140R (8/1,281;0.62%), E92G (2/1,281;0.16%), R263K (5/1,281; 0.4%), N155H (1/1,281; 0.08%), P145S (1/1,281;0.008%). Among the ART-experienced individuals, major INSTI RAMs detected were E138K (4/3,863; 0.10%), G140R (25/3,863;0.65%), G118R (2/3,863, 0.05%), R263K (4/3,863, 0.10%), T66I (1/3,863;0.03%), E138K + G140R (1/3,863, 0.03%|), G140R + R263K (1/3,863, 0.03%). High-level resistance to cabotegravir (CAB), elvitegravir (EVG), and raltegravir (RAL) was detected in 0.70, 0.16 and 0.06% of the individuals, respectively. Notably, bictegravir (BIC) and dolutegravir (DTG) showed no high-level resistance. Conclusion The overall prevalence of archived INSTI RAMs in Botswana was low prior to transitioning to first-line DTG-based ART regimens, and did not differ between ART-naïve and ART-experienced individuals. Ongoing surveillance of INSTI DRMs in Botswana will allow for re-assessment of INSTI resistance risk following nationwide DTG rollout.